Pembelajaran Daring: Depresi dan Kecemasan Pada Mahasiswa Selama Pandemi COVID-19 - Anggun Budiastuti (Kampurui Jurnal Kesehatan Masyarakat, 2021)
This study aimed to assess depression and anxiety and to analyze the impact of online learning on depression and anxiety among students. Online-based cross sectional study with snowballing sampling method was conducted among 442 students enrolled at graduate level in universitas sriwijaya. Students were asked to fill out a survey which was available in googleform link shared through whatsapp and others social media platform. The prevalence of depression and anxiety was 40% and 60,1%, respectively, range from mild, moderate and severe symptoms. The study showed significant associatios between online learning and depression (PR=1,79 95% CI 1,15-2,79)and anxiety(PR=1,78 95% CI 1,11-2,87. Based on research findings that showed a high prevalence of depression and anxiety among students during the COVID-19 pandemic, psychological counseling was needed to minimize students mental health risks.